Pediatric Collections: Social Determinants of Health (Part 3: Promoting Health Equity) 2022
DOI: 10.1542/9781610026390-part03-cross_sector_approach
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sector Approach Expands Screening and Addresses Health-Related Social Needs in Primary Care

Abstract: OBJECTIVES During infancy, the American Academy of Pediatrics Bright Futures fourth edition health supervision guidelines recommend frequent well-child visits (WCVs) in which providers are expected to screen for and address maternal depression, intimate partner violence (IPV), and health-related social needs (HRSN). We spread an evidence-based approach that implements these recommendations (Developmental Understanding and Legal Collaboration for Everyone; DULCE) with 3 aims for 6-month-old in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A review by Gottlieb et al [68] identified 37 programs aimed at addressing family social and economic needs, but these evaluations were largely focused on process measures like referral rate and effect on social determinants of health rather than health outcomes, utilization, or cost [69]. For example, whereas screening for health-harming legal needs and referral to medical–legal partnerships has been associated with positive legal outcomes and improvements in social determinants of health, studies linking this process to decreased acute healthcare utilization and health outcomes are limited [70 ▪ ,71,72 ▪ ]. Although larger scale intervention studies are underway, a standardized approach to evaluation, particularly in pediatrics, is still lacking [73].…”
Section: Health Outcomes and Valuementioning
confidence: 99%
“…A review by Gottlieb et al [68] identified 37 programs aimed at addressing family social and economic needs, but these evaluations were largely focused on process measures like referral rate and effect on social determinants of health rather than health outcomes, utilization, or cost [69]. For example, whereas screening for health-harming legal needs and referral to medical–legal partnerships has been associated with positive legal outcomes and improvements in social determinants of health, studies linking this process to decreased acute healthcare utilization and health outcomes are limited [70 ▪ ,71,72 ▪ ]. Although larger scale intervention studies are underway, a standardized approach to evaluation, particularly in pediatrics, is still lacking [73].…”
Section: Health Outcomes and Valuementioning
confidence: 99%